Alfred Buckowski working at control board at Hercules Parlin plant - Hercules Incorporated (1959)
General view of employee Alfred Buckowski working at a control board used to manage the continuous nitration operation at the Hercules Powder Company plant in Parlin, New Jersey. The nitration process has many industrial applications and is notably used for the production of explosives. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Propellants; Nitration; Hercules Incorporated; Corporations; Control boards (Electrical engineering); Buckowski, Alfred